(NkATALOG CUNAMI NA WOSTO^NOM POBEREVXE tIHOGO OKEANA (B(1513 - 1968(NGG(B.) /s - (NsOLOWXEW(B, (NsERGEJ lEONIDOWI^s; (NgO ~AN nAMs; (NsAWARENSKIJ(B, (Ne(B.(Nf(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1975)
(NlIT(B. (NI SOKRA](B.: (NS(B. 193 - 203s
(Nan sssr(B. (NmEVDUWED(B. (NSOWET PO SEJSMOLOGII I SEJSMOSTOJKOMU STROITELXSTWU(B, (NsAHALINSKIJ KOMPLEKSNYJ NAU^NO(B-(NISSLEDOWATELXSKIJ IN(B-(NT dALXNEWOSTO^NOGO NAU^NOGO CENTRAs
Keywords: (NkATALOGIs; (NtIHIJ OKEANs; (NcUNAMIs